1941
DOI: 10.1084/jem.74.6.611
|View full text |Cite
|
Sign up to set email alerts
|

The Bactericidal Action of Synthetic Detergents

Abstract: 1. The bactericidal action of a number of anionic and cationic synthetic detergents on four Gram-positive and three Gram-negative bacteria has been investigated. 2. Cationic detergents, as a group, were found to exhibit marked bactericidal effects on Gram-positive microorganisms and somewhat less pronounced action on Gram-negative organisms. 3. The anionic detergents were germicidal only against the Gram-positive organisms, and they were considerably less effective than the cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1945
1945
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(19 citation statements)
references
References 8 publications
3
15
1
Order By: Relevance
“…In comparison, the anionic surfactant SDS did not appear to discriminate. Similar results regarding the differing susceptibilities of Grampositive and Gram-negative organisms to anionic surfactants have been reported previously [31,32]. Such differences are usually attributed to the differences in the cell wall.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, the anionic surfactant SDS did not appear to discriminate. Similar results regarding the differing susceptibilities of Grampositive and Gram-negative organisms to anionic surfactants have been reported previously [31,32]. Such differences are usually attributed to the differences in the cell wall.…”
Section: Discussionsupporting
confidence: 88%
“…It then disrupted the cell wall and increased permeability (Baker et al, 1941). Despite the well-established therapeutic effects of a CPC mouthwash, in this study we found that low concentration of CPC had low activity to inhibit Candida activities.…”
Section: Resultscontrasting
confidence: 57%
“…This supports the hypothesis, previously raised by Baker et al, of cell membrane disorganization by detergent-like activity as the main mode of action of QACs. [35] More than 50 years later, Denyer also found that the main effects of QACs in bacteria are structural and functional changes in the cell wall, release of wall components and initiation of autolysis, inhibition of membrane ATPase, and electrostatic interactions with negatively charged polar head groups of phospholipids. [36,37] In another study by Locher et al, [38] the antimicrobial properties of nostocarbolines (see Figure 7 below) were investigated; these compounds were observed to exhibit activities only as dimers.…”
Section: Targets Of Qacs In Bacteria: More Than Nonspecific Interactimentioning
confidence: 99%